IMPLEMENTATION OF THE EMERGENCY POLICY FOR HANDLING COVID-19 THROUGH PEPRDA NUMBER 10 OF 2020 IN THE PROVINCE OF THE BANGKA BELITUNG ISLAND - Hendry Jan; Kgs. M. Sobri; Alfitri . (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to analyze the implementation, supporting factors, and inhibiting factors in implementing emergency policies through Perda Number 10 of 2020. The research method used is a qualitative descriptive method. The results of the organizational research show that the Provincial Government has formed a Covid-19 Task Force Team which continues to communicate and coordinate with all parties. However, the lack of personnel makes the implementation of regional regulations less than optimal in the field. In interpretation, the local government does not form a special small team tasked with explaining or describing in detail the articles in the regional regulation. Judging from the application, the implementation of the Perda is related to the procedures and working procedures of the policy which are usually related to the guidelines for implementing the policy. Through this study, it can be concluded that the implementation of the emergency policy of Regional Regulation Number 10 of 2020 concerning the Adaptation of New Habits in the Prevention and Control of the 2019 Corona Virus Disease has not been fully carried out to the maximum for the community, especially among the lower middle class. However, to support and make the implementation of the regional regulation a success, a vaccination program was carried out which spread to all areas in the Bangka Belitung Islands, from cities to remote villages.